A institucionalização dos sistemas municipais de ensino na realidade paraense: obstáculos e possibilidades - o caso do Município de Barcarena - PEREIRA, Maria do Socorro Vasconcelos (Universidade Federal do Pará, 2012)
The study on the Institutionalization of the Municipal Systems of Education in the reality of Para: obstacles and difficulties - the case of the Municipality of Barcarena aimed to investigate the factors that hinder the establishment of the Municipal Council of Education in Barcarena (State of Pará, Brazil) in order to identify whether obstacles have financial, political or technical character. Documentary analysis and interviews were the instruments used to meet the proposed objectives. Data gathering and processing prioritized the analysis of laws, decrees, opinions, regulations, government plans, educational projects and programs, as well as the contents of interviews with individuals involved in the educational process. The research results allow to infer that the institutionalization of the Municipal System of Education in Barcarena requires that the municipal administration be willing to break off with the patrimonial character of government practices, since there is no guarantee of democratization only through the creation of the Municipal System of Education, or of other elements comprised in the educational administration, without a process through which public management be grounded upon collective participation. The immediate demand requires autonomy for the construction of educational policies that address the municipal reality; mechanisms that allow for the participation of society in both the deliberations, the monitoring bodies, and in the social control of resources for education, through the various groups represented; the overcoming of the concept of public space as private property; and the training, qualification of technical staff to carry out the decisions concerning municipal education. Such a demand constitutes a challenge, given the strong presence of conflicts and power struggles between representatives of civil society and those of both the municipal executive and legislative forces, which may be seen as a positive factor should it be understood as a possibility for the construction of educational policies rooted in the diversity of opinions, because different segments of Barcarena‘s civil society show their interest to participate. Some of them are mobilizing more actively, others in smaller proportions, but the need remains that they be recognized as social subjects, and that the theoretical, pedagogical and political education be also included as a key factor for their participation in social mobilization, actions in order to organize the Municipal System of Education, parallel to the recognition that it is a right that needs to be consolidated.